The Estimation of Blood Platelet Survival - Murphy, E. A; Francis, M. E (Thrombosis and Haemostasis, 1969)
Since migrating cells cannot be individually identified, inferences about their pattern of survival must be based on the collective behavior of a defined group of such cells. A precise nomenclature for the aspects of such cells and their behavior is necessary. Accurate estimates of mean survival of cells depend on the use of a model, which can only be constructed by considering pertinent factors in the internal and external economy of the cell. But demonstration that a factor is indeed pertinent depends in large part on observing change in mean survival. This circularity may be avoided by studying those properties of such survival curves which are uninfluenced by the form of the distribution of cell survival. Since these properties are logical necessities, there is no need to verify them experimentally.